Case report: The devil was hidden in the mastocytes – an unusually fulminant case of indolent systemic mastocytosis in a 45-year-old patient, missed for almost 20 years - Boukouris, Aristeidis E.; Michelakis, Ioannis; Metaxas, Dionysios; Karapati, Gianna; Kanellis, George; Lioni, Athina; Tzavara, Vasiliki (Frontiers in Immunology, 2023)
Indolent systemic mastocytosis (ISM) represents the most common form of SM, typically following a slow clinical course. While anaphylactic reactions may come up in the life course of an ISM patient, these are often moderate and do not pose a threat to patient’s health. Here, we present an undiagnosed case of ISM with recurrent severe anaphylactic episodes following consumption of food and emotional stress. One of these episodes led to anaphylactic shock, necessitating temporary mechanical ventilation and intensive care unit (ICU) support. Besides hypotension, a diffuse, itchy, red rash was the only notable clinical finding. Upon recovery, we found abnormally high baseline serum tryptase level as well as 10% bone marrow (BM) infiltration by multifocal, dense clusters of CD117+/mast cell tryptase+/CD25+ mast cells (MCs), consolidating the diagnosis of ISM. Prophylactic treatment with a histamine receptor antagonist was initiated, resulting in milder episodes thereafter. Diagnosis of ISM requires a high level of suspicion; its prompt recognition and treatment are important in preventing potentially life-threatening anaphylactic episodes.